Intermix of metal nanoparticles–single wall carbon nanotubes. Issue 54 (23rd June 2017) - Xu, Feng; Lu, Qin; Ye, Lin; Tsang, S. C. Edman
Abstract : Separated metal islands with no inter-atomic mixing on single walled carbon nanotubes exhibit electrocatalytic properties comparable to corresponding nanoalloy structures. Abstract : Using physical mixtures of Pd/SWNTs (Pd nanoparticles on single-walled carbon nanotubes) and Pt/SWNTs, the composites show electro-catalytic properties comparable to the corresponding alloys: electron exchange readily occurs between the two metal nanoparticles via SWNT support at long ranges without direct atomic contact, which is responsible for the tunable alloy-like properties.